“This is my fate, this is a woman’s fate” : Marital Status and Female Sexuality as Sites of Patriarchal Power in J.M. Coetzee’s In the Heart of the Country - Nokkala, Eerika (My University, 2022)
In this thesis I examine marital status and female sexuality as sites of patriarchal power in J.M. Coetzee’s novel In the Heart of the Country (1976, 1977). Literature conveys and preserves meaning, and the portrayals of womanhood and subordinate social status of women presented in mythology continue to live on to date, thus the importance of reflecting on potentially harmful projections being presented as normative becomes essential. The framework of seminal feminist thinking by Kate Millett in Sexual Politics (1969, 1970) and Simone de Beauvoir in The Second Sex (1949) acts as the basis of my theorisation of a woman’s positioning in patriarchal systems. The life of narrator and protagonist Magda is overshadowed by her experienced failures as a woman and her spinster fate, both deeply intertwined with societal conditioning and a woman’s purpose resting on her reproductive function. The family unit of the farm in colonial South Africa is the main source of social power and is the main enforcer of patriarchal values. Female sexuality is depicted through Magda as wrong and inappropriate, with the purpose of serving a man’s needs. The depictions of sexual violence experienced by Magda and Klein-Anna, the farmhand’s wife, vary greatly in respect to victimhood and agency, portraying the intersecting hierarchies produced through gender, race and socioeconomic status, which is the epitome of patriarchal systems and colonialism.
Keywords: patriarchy, sexuality, marriage, womanhood, feminism